2010
DOI: 10.1158/1078-0432.ccr-09-2301
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors and 15-Deoxy-Δ12,14-Prostaglandin J2 Synergistically Induce Apoptosis

Abstract: Purpose: The clinically relevant histone deacetylase inhibitors (HDI) valproic acid (VPA) and suberoylanilide hydroxamic acid exert variable antitumor activities but increase therapeutic efficacy when combined with other agents. The natural endogenous ligand of peroxisome proliferator-activated receptor γ 15-deoxy-Δ 12,14 -prostaglandin J 2 (15d-PGJ 2 ) is a potent antineoplastic agent. Therefore, we investigated whether these HDIs in combination with 15d-PGJ 2 could show synergistic antitumor activity in colo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…Our findings point to distinct growth blocking properties of Vpa on colon tumor cells in vitro and in vivo, which are in accordance with previous reports that hdac inhibition triggers growth inhibition of colon cancer cell lines alone or in combination with other drugs (10,11). Of note, the antiproliferative effect of Vpa in vivo peaked between treatment days 17 and 21. thereafter, the treatment effect subsided slightly as tumor growth increased again at day 24 of the administration period.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings point to distinct growth blocking properties of Vpa on colon tumor cells in vitro and in vivo, which are in accordance with previous reports that hdac inhibition triggers growth inhibition of colon cancer cell lines alone or in combination with other drugs (10,11). Of note, the antiproliferative effect of Vpa in vivo peaked between treatment days 17 and 21. thereafter, the treatment effect subsided slightly as tumor growth increased again at day 24 of the administration period.…”
Section: Discussionsupporting
confidence: 92%
“…Apoptosis was induced in colorectal cancer cells following treatment with the dehydration product of PGD 2 , 15d-PGJ 2 [116]. This observation was supported by a number of further studies, both in CRC and other cancer types [117][118][119][120][121][122]. These subsequent studies also identified that 15d-PGJ 2 treatment induced cell-cycle arrest [118].…”
Section: Regulation Of Apoptosis By Eicosanoidsmentioning
confidence: 65%
“…Histone deacetylase (HDAC) inhibitors are promising anticancer agents that induce growth arrest, differentiation and apoptosis in various types of tumor cell lines (7,8). We identified OBP-801, also known as YM753, as a novel HDAC inhibitor with attractive pharmacodynamic and pharmacokinetic properties by screening for a p21 WAF1/Cip1 -inducing agent (9).…”
Section: Introductionmentioning
confidence: 99%